(untitled) (Advancements in Homeopathic Research, 2025)
Alopecia areata, commonly known as spot baldness, is a condition where hair loss occurs in small, circular patches on the scalp or other areas of the body. This autoimmune disorder affects approximately 1-2% of the global population and can develop at any age [1]. Typically, it results in coin-sized bald spots on the scalp, but the condition’s course is unpredictable, leading to various forms such as alopecia totalis, alopecia universalis, and ophiasis. Although it is an autoimmune condition, traditional medical treatments often lead to relapses and come with potential side effects. This case involved a 15-year-old female patient who sought treatment at the National Institute of Homoeopathy (N.I.H) outpatient department (OPD) for alopecia areata. The patient underwent individualized homeopathic treatment for seven months, resulting in a complete recovery without any adverse effects. Throughout the treatment process, both the MONARCH score and objective clinical evidence demonstrated significant improvement, confirming the effectiveness of homeopathic treatment. The individualized selection of homeopathic remedies, based on the totality of the patient’s symptoms, proved to be a valuable approach in achieving successful outcomes. This case report highlights the potential of homeopathy in managing alopecia areata, particularly in cases where conventional treatments may fail to provide consistent results or cause unwanted side effects. The positive response observed in this patient supports the role of homeopathy as a promising therapeutic option for this challenging condition